Chemotherapy-induced peripheral neuropathy: review for clinical practice - Delma Aurélia da Silva Simão; Munir Murad; Carolina Martins; Viviane Cristina Fernandes; Karine Marley Captein; Antonio Lúcio Teixeira (Revista Dor)
ABSTRACTBACKGROUND AND OBJECTIVES:Chemotherapy-induced peripheral neuropathy is the most common neurological syndrome secondary to antineoplastic therapy primarily affecting patients being treated with taxanes and platinum derivatives. Sensory neuropathy is the most frequent type. This study aimed at carrying out a narrative review of the literature on the pathophysiology, clinical manifestations, impact, evaluation, diagnosis treatment and prevention of chemotherapy-induced peripheral neuropathy.CONTENTS:Recent studies have shown association among inflammatory molecules, oxidative stress and development of chemotherapy-induced peripheral neuropathy. Most frequent symptoms are limbs numbness and tingling, with neuropathic pain having significant impact on the functionality of patients submitted to antineoplastic therapy. Several evaluation tools have been tested, being electroneuromyography considered the golden standard for chemotherapy-induced peripheral neuropathy diagnosis. There are different pharmacological strategies for its therapy and prevention.CONCLUSION:It is known that chemotherapy-induced peripheral neuropathy is a frequent syndrome negatively interfering with cancer patients’ treatment and quality of life. Different drugs are associated to different risk levels, which show its neurobiological complexity. Prevention, diagnostic and treatment strategies have to greatly evolve to minimize its frequency and severity.